The effect of wheel polygonal wear on temperature and vibration characteristics of a high-speed train braking system. (1st March 2023) - Zhang, Liang; Wang, Zhiwei; Wang, Quan; Mo, Jiliang; Feng, Jian; Wang, Kaiyun
Highlights: A rigid-flexible coupled vehicle system dynamics model is established, which considers the flexible deformation of the brake disc and wheelset as well as wheel polygonal wear. A thermo-mechanical coupled finite element model of a high-speed train braking system is established, which takes into account nonlinear friction, wheel-rail excitation and thermo-mechanical coupled characteristics. The accuracies of the dynamics model and finite element model are verified by line and bench tests, respectively. The effects of measured wheel polygonal wear and wheel polygonal wear order on the temperature and vibration characteristics of braking system are analyzed. Abstract: To study the effect of wheel polygonal wear (WPW) on temperature and vibration behaviours of a high-speed train braking system, a rigid-flexible coupled vehicle system dynamics model and a thermo-mechanical coupled finite element (FE) model of a braking system are developed in this study. The accuracy of the vehicle dynamics model and FE model are verified by line and bench tests, respectively. The dynamic interactions between different vehicle components, and the nonlinear factors such as wheel − rail interactions, non-linear damper and disc − block frictions are comprehensively considered in the model, which is able to more realistically reflect the service environment of a vehicle system and accurately capture the vibration, temperature and disc − block contact status of a braking system during braking process. Based on the established models, the dynamic behaviours of the braking system excited by WPW is systematically investigated. The results indicate that the standard deviation (SD) of contact area, the root mean square (RMS) values of vibration and the temperature of friction block interface with WPW are much higher compared to those without WPW. Besides, the braking system experiences more intense vibration with the increment of WPW order.